EFEKTIVITAS PELAYANAN SURAT IZIN USAHA PERDAGANGAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPM-PTSP) KABUPATEN KAMPAR - Selvia Riza; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Investment services and integrated one stop services (DPM-PTSP) delegated 17 licensing and non-licensing Kampar regent by regulation No. 2 of 2013 regarding the delegation of authority to the Head of Department of Investment and Integrated One stop services . One licensing namely Trade Permit (License), Handling of Trading Business License at districts Bangkinang City more than Districts Bangkinang.The research aimed is to dtermine the effectiveness of service busines license in the investment services and integrated one stop services (DPM-PTSP) in Kampar. According to Duncan, there are three criteria for measuring the effectiveness is achievement of objectives, integration, and adaptation. While the factors that influence the effectiveness of service is leadership, personnel resources, public awareness and facility. This study use description based on the data that was collected in the field, them the presentation of data can describe the results of interviews and observation will then be deduced.The results of this study indicate that the investment services and integrated one stop services (DPM-PTSP) in Kampar have been effective in providing services to the public especially busines lisence. More subdistrict Bangkinang City manage licensing because for subdistric Bangkinang city more aware of the importance of licensing, and often follow socialization conducted by in the investment service and integrated one stop service, as well as many community businesses domiciled in the district of the Bangkinang City.Key Words : Effectiviness, Service, Busines Lincense